تسويق نبات القبار في البادية السورية - ديوب معمر; صقر إبراهيم; محمد موفق; خنيفس علي; حبيب وائل (Latakia University Journal -Biological Sciences Series, 2019)
أجريت هذه الدراسة في بادية حماة خلال موسم (2007-2008) على عينة عشوائية من العاملين في جمع نبات القبار، بلغت 220 عائلة و210 عمال، من خلال استمارة أعدت خصيصاً لهذا الغرض. وقد هدفت هذه الدراسة إلى معرفة الخصائص الاجتماعية والاقتصادية للعاملين في هذا المجال، وإبراز مساهمة العامل البشري في عمليات جني ثمار نبات القبار، ودراسة القنوات التسويقية وتحديد أهم المسالك التسويقية لهذا المحصول. بينت النتائج أن للقبار طرقاً تسويقيةً مختلفةً تسود فيها طريقة بيع القبار من المنتِج إلى مراكز التجميع المنتشرة في المواقع المستهدفة، ويتم تسعير المُنتَج من قبل التاجر بناءً على العرض والطلب العالمي، ويأخذ أصحاب مراكز جمع القبار عمولة تتراوح مابين 5-7 ل.س/كغ، وتراوحت أسعار القبار مابين 65-75 ل.س/كغ، كذلك تقوم بعض العائلات بجمع وتسويق المنتج ذاتياً للاستفادة من القيمة المضافة المأخوذة من قبل أصحاب مراكز التجميع. وبينت الدراسة أن الدخل العائلي من جمع القبار بلغ نحو 50 ألف ل.س في الموسم، الأمر الذي يدل على الأهمية الاقتصادية لهذا النبات، وإن أفضل نموذج تسويقي لنبات القبار يتمثل في بيع المُنتَج إلى التاجر مباشرة. وخلصت الدراسة إلى أهمية التركيز على العائلات التي تقوم بإنتاج وتسويق المنتج بنفسها لإنشاء مركز تجميع وتسويق على مستوى التجمعات المستهدفة لتحقيق أعلى دخل للعائلة خلال موسم الجني. This study was conducted in Badiya of Hama during the season (2007-2008) on a random sample of families 220 and workers 210 collecting Alkabbar plant, using a specially designed questionnaire. The purpose of this study was to investigate social and economic characteristics of workers in this area and highlight the contribution of gender in collecting Alkabbar plant, and to study the marketing channels and identify the most important channel for the marketing of this crop. The results showed that the Kabbar has different marketing ways, including the method of sale of Alkabbar product to collection centers located in the targeted sites. The product is priced by the trader depending on the global supply and demand, and the owners of collection centers charge a commission fee ranging between 5-7 for .S.L / kg. Prices of Alkabbar ranged between 65-75 for .S.L / kg. However, some families collecting the product market it themselves save the fee. The study also showed that family income from Alkabbar collection was about 50.000 S.L per season. Thus, the plant has an important the economic value, and the best marketing model is for families to sell the product directly to the trader. The study suggests focusing on families that produce and market the product themselves by creating a collection center at the level of the targeted populations to achieve higher income for the family during the harvest season.